Chefias de estado brasileira e norte-americana: uma microcomparação dos institutos que permeiam o poder político representativo do Estado - Alonso, Pedro Henrique de Carvalho Silva (2025)
In this dissertation, the Heads of State of Brazil and the United States are analyzed. The research begins by outlining the historical trajectory of the development of political powers, followed by an examination of presidentialism as a system and its adaptation in Latin America and Brazil. Upon delving into the role of the Head of State itself, the study adopts a micro-comparative approach to understand the concentration of power within the American and Brazilian spheres, particularly in relation to the respective office. Throughout the work, the duties of the Head of State are evaluated; however, two key aspects proved crucial to the research conclusions: the authority to propose legislative initiatives and the power to declare states of exception. By the end, it becomes clear whether there is a greater concentration of power in the Brazilian institutional model or the American one